2019
DOI: 10.1111/cjag.12205
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in male and female farmers’ preference for a profit‐enhancing and labor‐saving technology: The case of Direct‐Seeded Rice (DSR) in India

Abstract: Labor-saving and income-increasing technologies may affect women farmers differently from men. However, very few studies explicitly account for women's preferences for new technologies. We carried out a discrete choice experiment with 337 female and 329 male farmers in Maharashtra, India, to measure their willingness to pay (WTP) for direct-seeded rice (DSR) with drum seeder and to understand the gender differences in marginal valuations of key attributes. We used the Women's Empowerment in Agriculture Index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 68 publications
(106 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, in many contexts, as documented for instance by Theis et al (2019), women's ability to engage with and benefit from laborsaving mechanization is limited by normative stereotypes that discourage women from operating machines and restrict their physical mobility and social interactions, and by normative expectations of women's deference to male authority. As several studies have found, women's bargaining power is often too limited to influence household adoption decisions (Joshi et al 2019;Hansda 2017;Rola-Rubzen et al (2020).…”
Section: Social Economic and Policy Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in many contexts, as documented for instance by Theis et al (2019), women's ability to engage with and benefit from laborsaving mechanization is limited by normative stereotypes that discourage women from operating machines and restrict their physical mobility and social interactions, and by normative expectations of women's deference to male authority. As several studies have found, women's bargaining power is often too limited to influence household adoption decisions (Joshi et al 2019;Hansda 2017;Rola-Rubzen et al (2020).…”
Section: Social Economic and Policy Implicationsmentioning
confidence: 99%
“…The introduction of MTR and DSR may have positive or negative impacts on men and/or women farmers, which is determined by their social positioning and how they maneuver change. Literature shows that DSR reduces labor requirements, increases yield and profitability, saves seeds, and reduces carbon emissions (Joshi et al 2019). As such, technological solutions to mitigate GHG emissions and reduce drudgery have opportunities and trade-offs for equitable benefits (Beuchelt and Badstue 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of household decision-making related to mechanical rice transplanting (MRT) in Indiaa technology reducing labor in transplanting, primarily done by womenfound that women value MRT more than men do (Gulati et al, 2019). However, overall household demand articulation exclusively reflects men's valuation of the technology, as women's bargaining power is too limited to influence the adoption decision (Joshi et al, 2019).…”
Section: Gender Differences and Adoption Of Laborsaving Agricultural Technologiesmentioning
confidence: 99%
“…People's expectations of how a new technology will affect social relations, roles, and responsibilities also influence technology adoption (Doss, 2001;Peterman et al, 2014, Theis et al, 2019. Several authors emphasize that households do not act in a unitary manner when making decisions or allocating resources; and women and men within households do not always share preferences nor resources (Alderman et al, 1995;Doss 2014;Doss & Kieran, 2014;Joshi et al, 2019;Meinzen-Dick et al, 2011). Households have dimensions of both cooperation and conflict (Agarwal, 1997;Jackson, 2013;Sen, 1990), and intra-household decision-making is shaped by power relations and negotiation between household members.…”
Section: Gender Differences and Adoption Of Laborsaving Agricultural Technologiesmentioning
confidence: 99%